Prognostic value of circulating tumor DNA and copy-number alterations in patients receiving tandem [225Ac]Ac-/[177Lu]Lu-PSMA-617 therapy for metastatic castration-resistant prostate cancer: a prospective observational study - Mariam Amghar; Thomas Hielscher; Tobias Rausch; Hilal Özgür; Ulrike Bauder-Wüst; Hendrik Rathke; Frank Bruchertseifer; Alfred Morgenstern; Mareike Roscher; Vladimír Beneš; Clemens Kratochwil; Martina Benešová-Schäfer (BMC Cancer, 2026)
Abstract Background Prostate-specific membrane antigen-targeted radioligand therapy (PSMA-RLT) demonstrates clinical efficacy in metastatic castration-resistant prostate cancer (mCRPC), yet robust biomarkers for dynamic treatment monitoring and resistance remain lacking. We investigated circulating tumor DNA (ctDNA)-derived tumor fraction (TFx) and genome-wide copy-number alterations (CNAs) as non-invasive biomarkers of treatment response and resistance biology. Methods Seventy-eight patients with advanced mCRPC receiving tandem [ 225 Ac]Ac-/[ 177 Lu]Lu-PSMA-617 were prospectively enrolled. Plasma samples collected longitudinally ( n = 172) underwent ultra–low-pass whole-genome sequencing. TFx was estimated using ichorCNA, and recurrent CNAs were identified using GISTIC2.0. Associations with progression and overall survival (OS) were assessed using Cox proportional hazards models, including time-dependent analyses. Results Baseline TFx differed across metastatic disease stages ( p = 0.027) and dynamic TFx changes paralleled PSA kinetics during early treatment. Modelled as a time-dependent variable, TFx was associated with a significantly increased risk of progression (HR 4.9, 95% CI 1.2–20.1, p = 0.026). Unsupervised clustering identified distinct high- and low-CNA burden groups strongly correlated with TFx ( p = 8.09 × 10⁻ 8 ). High CNA burden was associated with shorter median OS (8.3 vs 13.8 months). Multivariable analysis identified baseline logPSA and logALP as independent predictors of OS. Recurrent CNAs affected key tumor suppressors (PTEN, RB1, BRCA2, ATM) and were enriched in pathways related to TP53 signalling, homologous recombination repair, and oncogenic signaling. Longitudinal analyses demonstrated persistence and expansion of specific amplifications at progression. Conclusions ctDNA-derived TFx represents a dynamic biomarker of treatment response and progression risk, while CNA profiling provides insight into resistance mechanisms in mCRPC treated with PSMA-RLT. These findings support the integration of ctDNA-based biomarkers into clinical stratification and real-time monitoring strategies.